Spawning and developmental biology of vulnerable catfish, Wallago attu : Implications for quality seed production and stock replenishment - Saeed Akram Khan; Muhammad Khalil Ahmad Khan; Shahid Sherzada (Journal of Fish Biology, 2026)
Freshwater catfish, Wallago attu , is a popular fish species due to its excellent taste and low quantity of intramuscular bones. Scientific and evidence‐based studies on the embryonic and larval development of this vulnerable fish species are limited. We attempted artificial breeding using Ovaprim, and photographs of the embryological events were taken, revealing each stage of early development. For this, a sequence of microscopic analysis was performed using a trinocular digital microscope. Time‐lapse imaging was also performed to calculate the duration of each developmental stage. The eggs were spherical, and highly adhesive, with a diameter of 1.74 ± 0.11 in T1 and T2, 1.86 ± 0.17 and 1.8 ± 0.16 in T3 and T4, respectively. Hatching occurred at 979.33 ± 5.13, 973 ± 21.07, 981.67 ± 11.93 and 969 ± 7.21 min post‐fertilization (mpf) in T1, T2, T3 and T4, respectively. During embryonic development, the blastodisc appeared at 55.33 ± 4.04 (T1), 54.67 ± 5.13 (T2), 58.33 ± 3.79 (T3) and 58.33 ± 3.51 (T4). First cleavage appeared at 64.33 ± 2.08 (T1), 63.67 ± 5.03 (T2), 68 ± 1 (T3) and 66 ± 4.36 (T4) mpf, resulting in two equal blastomeres. Embryonic body movements started at 652 mpf. Free body embryonic development (ranging from the two‐cell to the pre‐hatching stage) took 810 mpf. Hatching occurred at 979.33 ± 5.13 (T1), 973 ± 21.07 (T2), 981.67 ± 11.93(T3) and 969 ± 7.21(T4) mpf, with average larval lengths of 4.88 ± 0.19 (T1), 5 ± 0.16 (T2), 4.88 ± 0.19 (T3) and 4.88 ± 0.28 (T4) mm. Such information will have significant implications on conservation and sustainable seed production of this species. The findings of this study will contribute to the advancement of W. attu aquaculture by providing valuable insights into quality seed production and stock replenishment.